Transnationality and diaspora advocacy: lessons from disaster. Issue 1 (2nd January 2016) - Esnard, Ann-Margaret; Sapat, Alka
ABSTRACT: A number of catastrophic disasters in the last decade have raised questions about their transnational impacts and about the role of the diaspora. The 2010 Haiti earthquake, the focus of our study, provided a lens to further our understanding of evolving conceptualizations about transnationalism, transmigrants, and social capital. We hypothesize that sustained 'intensive transnationalism' by diaspora and linking forms of social capital between diaspora, other civil society organizations and advocacy groups, and government institutions are critical during post-disaster recovery in affected nation states and in countries to which survivors turn for refuge. We conducted 103 in-depth, semi-structured interviews with a wide range of civil society actors in South Florida, Boston, New York, Atlanta, and Washington DC between June 2010 and June 2015. We found that linking forms of social capital were more important after the earthquake than in previous disasters. Overall, the longevity and variety of Haitian diaspora advocacy work, particularly in immigration, have resulted in broader social networks and alliances, work groups, task forces, interfaith coalitions, and support groups to address complex social and policy issues.